The Influence of Implementation of Sustainability Accounting and Management Participation on Employee Performance in the Bina Sejahtera Badung Employee Cooperative - SANJAYANI, Made Wulan Guna Harta; SAPUTRA, Komang Adi Kurniawan; SURASMI, Ida Ayu (PT Keberlanjutan Strategis Indonesia, 2024)
The purpose of this research is to determine the effect of implementing sustainability accounting and management participation on employee performance at the Bina Sejahtera Badung Employee Cooperative. The samples in this research were all employees of the Bina Sejahtera Badung Employee Cooperative with a total of 52 samples used in this research. This research uses primary data, data was collected by distributing questionnaires to the entire research sample. Testing research hypotheses using SPSS 26.0 for Windows. The research results show that the implementation of sustainability accounting (X1) has a positive and significant effect on employee performance (Y) at the Bina Sejahtera Badung Employee Cooperative and sustainability participation (X2) has a positive and significant effect on employee performance (Y) at the Bina Sejahtera Badung Employee Cooperative. Regression equation in this study are as follows: Y = 2.188 + 0.336 X1 + 0.373 X2. Based on these results, to optimize employee performance, policies and regulations are needed to improve the implementation of sustainability accounting and management participation.